Avaliação do mecanismo de transformação do revestimento galvanizado GA no aço 22MnB5 durante o processo de estampagem a quente - Henrique Lacerda Eleutério (2019)
Galvannealed steel (GA) has been successfully applied in the hot stamping process and their consumption is expected to increase in the coming years, mainly due to their excellent surface quality and galvanic resistance in relation to other types of coating. The main challenge for the galvanized steels consumption increase is to ensure the structural integrity of the coating layer containing Zn, without loss of Zn mass and to avoid the appearance of cracks induced by liquid metal (LME) during the hot forming process. In this study, the effect of the austenitizing heat treatment and hot stamping on the microstructure of the coating and its surface quality, microstructural integrity and crack formation of the steel were assessed in laboratory scale in order to obtain a product without defects. It was also evaluated the influence of the induction heater (IH) temperature on the surface quality and integrity of the coating and substrate after the forming process, in order to obtain the best operating conditions and to minimize the occurrence of defects in the coating surface and cracks mainly induced by LME. In this study, industrial samples will be processed using a muffle and a hot stamping press manufactured at Usiminas Research and Development Center (R&D). The samples will be analyzed using laboratory resources as scanning electron microscopy with coupled energy dispersive X-ray spectrometer (SEM / EDS), X-ray diffraction (XRD), glow discharge optical emission spectrometry (GDOES) and spectrometry of inductively coupled plasma (ICP-OES). The results showed that GA steels produced with IH temperature with 585ºC and isothermal soaking less than 35 s presented good surface quality, without LME cracks in the substrate, after hot stamping with austenitizing treatment with medium and high heat parameters and final process temperatures 910ºC and 930ºC.